2013
DOI: 10.1093/gerona/glt025
|View full text |Cite
|
Sign up to set email alerts
|

Informal Caregiving and the Risk for Coronary Heart Disease: The Whitehall II Study

Abstract: Caregiving in midlife is not in itself associated with greater risk of CHD, but it is associated with increased risk for CHD among caregivers who report being in poor health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 42 publications
1
71
1
1
Order By: Relevance
“…In addition, previous studies have reported informal caregivers as being at higher risk for coronary heart disease (CHD) and stroke than noncaregivers [43]. Caregivers who are in poor health may be at particular risk of developing CHD [44]. Poor self-care health behaviors [45] and heightened levels of chronic stress associated with inflammation [46] have been attributed to increased CHD risk in informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported informal caregivers as being at higher risk for coronary heart disease (CHD) and stroke than noncaregivers [43]. Caregivers who are in poor health may be at particular risk of developing CHD [44]. Poor self-care health behaviors [45] and heightened levels of chronic stress associated with inflammation [46] have been attributed to increased CHD risk in informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Caregiving has previously been suggested to increase the risk of ischaemic heart disease 37. However, a recent study from England indicated that caregiving was only associated with ischaemic heart disease among caregivers who were already in poor health at baseline 38. In our sample, the surviving husbands were, on average, over 75 years old at the study entry; thus, the caregiving burden could be of importance in explaining the results for the widowers.…”
Section: Discussionmentioning
confidence: 59%
“…; Buyck et al. ), and reduced preventive health behaviors (Son et al. ; Reeves, Bacon, and Fredman ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%